2011
DOI: 10.4103/0971-4065.83736
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, endothelial function, carotid artery intimal thickness and their correlates among chronic peritoneal dialysis patients

Abstract: We evaluated important nontraditional cardiovascular risk factors, endothelial function and oxidative stress (OS) among stable peritoneal dialysis (PD) patients. Their association with carotid intimal medial thickness (CIMT) was also assessed. Thirty-eight adult patients (13 diabetics, 20 males) on PD for >6 months and 15 age and sex-matched controls were studied. Duration of dialysis (DOD), residual urine output (UO), weekly Kt/V urea, detailed biochemical and lipid profile were noted. OS was measured by seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…A few studies reported increased OS among PD patients, but other prooxidants (TBARS, TAC) were measured, associated with hypoalbuminemic state or loss of residual renal function (RRF), and without comparing it with nondialysis CKD patients [ 25 , 27 , 30 ]. Khaira et al [ 31 ] found that PD patients have markedly impaired endothelial function as documented by impaired flow mediated dilatation of brachial artery with higher serum concentration of OS markers. Furthermore, Raju et al [ 29 ] confirmed significant increase in serum MDA in hemodialysis patients, compared with the same patients before they had started the hemodialysis treatment, which could be attributed to a bioincompatibility of dialysis membrane and diffusion of hydrophilic compounds to the dialysate and influx of endotoxin from the dialysate.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies reported increased OS among PD patients, but other prooxidants (TBARS, TAC) were measured, associated with hypoalbuminemic state or loss of residual renal function (RRF), and without comparing it with nondialysis CKD patients [ 25 , 27 , 30 ]. Khaira et al [ 31 ] found that PD patients have markedly impaired endothelial function as documented by impaired flow mediated dilatation of brachial artery with higher serum concentration of OS markers. Furthermore, Raju et al [ 29 ] confirmed significant increase in serum MDA in hemodialysis patients, compared with the same patients before they had started the hemodialysis treatment, which could be attributed to a bioincompatibility of dialysis membrane and diffusion of hydrophilic compounds to the dialysate and influx of endotoxin from the dialysate.…”
Section: Discussionmentioning
confidence: 99%
“…IMT and FMD measurements are reliable, reproducible and noninvasive technique to assess endothelial function as well as detecting and monitoring progression of atherosclerosis. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcaemia and the increased product of CaxP in PD patients are linked to the development of CCA calcification, especially in diabetic patients, independent of parathormone values [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Using multivariate analysis we found a statistically significant influence of CaxP product and the serum calcium on plaque score CCA. Hypercalcaemia and the increased product of CaxP in PD patients are linked to the development of CCA calcification, especially in diabetic patients, independent of parathormone values [ 18 ].…”
Section: Discussionmentioning
confidence: 99%